Cobalt Supply Chains: Global Responsibility for Children's Rights in the Democratic Republic of Congo - Delfia Putri Yanda; Iva Rachmawati (Journal Pena Wimaya, 2025)
This study examines child labour practices within the cobalt supply chain of the Democratic Republic of Congo (DRC) through the lens of the Global Production Network (GPN) framework. The findings indicate that, between 2018 and 2022, the DRC supplied over two-thirds of the world’s cobalt, with national reserves reaching 4 million metric tonnes, approximately 48% of global reserves. The Artisanal and Small-Scale Mining (ASM) sector contributes 15–30% of national production, yet operates with minimal regulation, rendering it highly vulnerable to exploitation. UNICEF (2014) estimates that around 40,000 children are engaged in cobalt mining, while the CLMRS recorded 5,346 child workers in two key provinces as of 2024. External interventions such as the COTECCO project have enhanced monitoring capacity (+38%), but regulatory implementation and certification remain largely administrative, lacking substantive transformation in governance. The GPN analysis highlights that disparities in value distribution and risk within the cobalt supply chain stem from the dominance of global actors, weak local governance, and fragmented cross-sectoral collaboration. This study underscores the necessity of global governance reform, local capacity strengthening, and genuine commitment from consumer countries and multinational corporations to ensure the protection of children’s rights and the creation of an equitable and sustainable cobalt supply chain. Keywords: cobalt, child labour, Global Production Network, global supply chain, governance